Local area networks : A business oriented approach - Goldman, James E.; Rawles, Phillip T. (New York ; Chichester : John Wiley and Sons, 2000)
Local area network infrastructure. Local area network software. Local area network connectivity. Local area network administration.
Keywords: Computer network; Client/server computing; Local area networks (Computer networks)